THE INFLUENCE OF CAPITAL STRUCTURE ON FIRM VALUE MODERATED BY PROFITABILITY: AN EMPIRICAL STUDY OF INFRASTRUCTURE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020–2024 (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Indonesia’s infrastructure sector has exhibited unstable performance in recent years, as evidenced by the fluctuating stock returns of infrastructure companies over the 2020 –2024 period. Such fluctuations underscore the instability of firm value and highlight the need to examine internal determinants, particularly capital structure and profitability, that may significantly influence firm value. This study aims to analyze the influence of capital structure on the value of companies with profitability as a moderating variable in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The company’s value is proxied using Tobin’s Q, capital structure is measured by Debt to Equity Ratio (DER), and profitability is proxied by Return on Assets (ROA). This research applies a quantitative approach with panel data regression analysis to capture the effect between variables more comprehensively. The sampling technique used was purposive sampling, resulting in 11 infrastructure companies that met the criteria during the observation period. The selection of the infrastructure sector is based on its strategic role in national economic development, as well as the fact that its performance in the capital market often attracts investors’ interest. The research findings show that, partially, capital structure has a significant positive effect on company value, indicating that the use of debt in financing decisions may be perceived positively by investors as a signal of growth potential. However, when profitability is tested as a moderating variable, the positive influence of capital structure on company value becomes weakened
Keywords: Firm Value; Profitability; Capital Structure